Financial Regulations and Innovations in Banking - Georgieva, Nadya (Economy and Business Yearbook, 2022)
In the contemporary world, new technologies are mostly characterized by digitization and digitization of socio-economic relations and processes. As digital services and technology are used in more and more aspects of our lives, the financial sector is not far behind this trend. Moreover, in the conditions of an ongoing global financial and economic crisis, innovative activity is particularly important for the survival and success of both a particular type of business and the economy as a whole. The banking sector is exposed to large-scale and rapid changes in technology. It is imperative for banks to be competitive and innovative. The need for legal regulations arises when financial innovations are introduced, and this is why the article will provide an overview of financial regulations and innovations and pay attention to fraud in electronic payments, as well as indicate the protection tools for payment operations in a digital environment.